Advancing Insights Into Diabetic Eye Disease: 5th Annual American Society of Retina Specialists Presidents' Young Investigator Award Lecture. (September 2019) - Conti, Thais F.; Singh, Rishi P.
Diabetes and its complications are an emerging public health crisis. Since vision changes can be irreversible in diabetic retinopathy (DR), early detection, recognition of prognostics, and treatment are important to prevent vision loss from DR. At the 2018 American Society of Retina Specialists (ASRS) Annual Meeting, Dr Rishi P. Singh was honored to receive the fifth annual ASRS Presidents' Young Investigator Award. This article summarizes many advancements in diabetic eye disease that we have witnessed recently covering the concepts of DR, disease pathogenesis, new imaging modalities, and improving treatment outcomes.